Pediatric Sepsis Markers: Interleukins and Others - Polic, B.; Dahlem, P.; Saraga, M. (Journal of Child Science, 2017)
Cytokines are a very important part in the regulation of immune response in sepsis. They are cellular signaling proteins whose production is a result of activation of specific receptors. Variations in the genes encoding cytokines have a significant role in interindividual susceptibility to sepsis and its severity, and their function may be modulated by age, gender, and some environmental factors. Cytokines are classified into the subsets of proinflammatory, anti-inflammatory, and multiple function cytokines. Regulated balance between proinflammatory cytokines, anti-inflammatory cytokines, and soluble inhibitors of proinflammatory cytokines is important for eliminating pathogens and reducing inflammation. High levels of some cytokines, such as tumor necrosis factor-α, interleukin (IL)-1, and IL-6, determine the course of disease and outcome in sepsis. Likewise, numerous other biomarkers may be potential indicators of sepsis, but none has been routinely used. The best approach to the diagnosis of sepsis is the combination of different biomarkers.
Keywords: sepsis; immune response; cytokines; other biomarkers